Addressing Gender in Higher Education Exit Exams: A Systematic Literature Review - Samson Worku Teshome (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Exit exams in higher education are crucial for certifying student competency and ensuring academic quality. However, growing attention has been directed toward gender-related disparities in exam performance, perceptions, and outcomes, raising concerns about fairness and equity in assessment practices. Objective: This systematic review aims to explore how gender influences students’ experiences with exit exams in higher education, focusing on performance, perception, and broader implications for equity and quality assurance. Method: Using the PRISMA framework, a comprehensive search was conducted across multiple academic databases. From an initial pool of 587 articles, 32 studies published between 1994 and 2024 were selected based on predefined inclusion criteria. Data extraction focused on study objectives, methodologies, contexts, and gender-specific findings. Result: The findings reveal that while female students often achieve performance levels equal to or higher than their male peers, they report elevated levels of test anxiety and face systemic biases that affect their exam experiences. Sociocultural norms, exam design, and institutional policies significantly contribute to these disparities. Conclusion: Gender differences in exit exam experiences underscore the need for inclusive and equitable assessment systems. Addressing these disparities requires reforms in exam design, support mechanisms, and institutional practices that account for gender-specific challenges. Contribution: This review contributes to the literature by systematically synthesizing evidence on gender and exit exams, highlighting the need for gender-sensitive assessment practices and offering recommendations for policy and educational reform in higher education.